Patient and public involvement toolkit - Cartwright, Julia; Crowe, Sally; Heneghan, Carl.; Perera, Rafael; Badenoch, Douglas; Wiley InterScience (Online service) (Chichester : Blackwell Pub., 2011)
Providing information to implement a new core healthcare requirement - patient involvementIncluding real case scenarios to illustrate the principles of effective PPIFollowing the unique Toolkit series format of flowcharts and layouts that guide the reader through each section.
What is patient and public involvement? -- How to conduct effective PPI -- Building relationships -- Evaluation of PPI -- The future of PPI.
Includes bibliographical references.
Print version record.
Keywords: Patient participation; Health planning; Patient Participation; Consumer Participation; Delivery of Health Care; HEALTH & FITNESS -- Health Care Issues; MEDICAL -- Public Health; MEDICAL -- Health Policy; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Diseases; SOCIAL SCIENCE -- Disease & Health Issues; MEDICAL -- Health Care Delivery; Health planning; Patient participation; Great Britain; Handbooks; Electronic books; Electronic resource